Genetically Modified Mosquitoes to Fight Malaria in Nigeria, Burkina Faso, Mali and Uganda: What Legal Response? - Lim Tung, Odile Juliette (Potchefstroom Electronic Law Journal, 2022)
Advanced applied research on genetically modified (hereafter GM) insects is being undertaken to control insect vectors of human diseases such as mosquitoes. GM insect technologies are being developed in countries where there is a legal framework for genetically modified mosquitoes (hereafter GMM), but the beneficiaries of such insect technologies to control insect-borne diseases are most likely to be in malaria-endemic countries where the regulation of GM insect technologies is inadequate. Although no commercial release of GMM has been conducted in Africa yet, there may be prospects for the use of GMM to control malaria in malaria-endemic countries such as Nigeria, Burkina Faso, Mali and Uganda. Nigeria has the highest rate of deaths related to malaria in Africa and will potentially be targeted by companies seeking to introduce GMM as a public health tool in African countries. Research is being carried out on GMM in Burkina Faso, Mali and Uganda in collaboration with foreign companies. Whereas the control of diseases is certainly needed and there are potential public health benefits for GM insect technologies to address mosquito control, there are environmental and health concerns, and there is also the potential of the misuse of such technologies. Consequently, the use of GMM requires prior robust domestic, regional and international regulation. While the Cartagena Protocol on Transboundary Movements of Living Modified Organisms (LMOs) to the Convention on Biological Diversity (hereafter the Cartagena Protocol) and voluntary guidelines on the testing of GM mosquitoes are applicable with respect to GM insect technologies, there is a lack of international and regional guidance on the regulation of such technologies. Domestic legislation tends to focus on GM crops and is inadequate for regulating GMM. This paper discusses the legal response for the above African countries which may perhaps use GMM as a public health tool and makes recommendations for the necessary regulatory response.